Answers : - Robinson, Paul W. (Lion House Press, 1983)
Answers: A Parents' Guidebook for Solving Problems, is the most comprehensive and dynamic parenting resourcebook available today. It is a must for all parents who are seriously interested in solving family problems or having a more positive impact on the lives of their children.